Ultrastructure of the Odontocete Organ of Corti: Scanning and transmission electron microscopy. Issue 3 (28th October 2014) - Morell, Maria; Lenoir, Marc; Shadwick, Robert E.; Jauniaux, Thierry; Dabin, Willy; Begeman, Lineke; Ferreira, Marisa; Maestre, Iranzu; Degollada, Eduard; Hernandez‐Milian, Gema; Cazevieille, Chantal; Fortuño, José‐Manuel; et al.
ABSTRACT The morphological study of the Odontocete organ of Corti, together with possible alterations associated with damage from sound exposure, represents a key conservation approach to assess the effects of acoustic pollution on marine ecosystems. By collaborating with stranding networks from several European countries, 150 ears from 13 species of Odontocetes were collected and analyzed by scanning (SEM) and transmission (TEM) electron microscopy. Based on our analyses, we first describe and compare Odontocete cochlear structures and then propose a diagnostic method to identify inner ear alterations in stranded individuals. The two species analyzed by TEM (Phocoena phocoena and Stenella coeruleoalba) showed morphological characteristics in the lower basal turn of high‐frequency hearing species. Among other striking features, outer hair cell bodies were extremely small and were strongly attached to Deiters cells. Such morphological characteristics, shared with horseshoe bats, suggest that there has been convergent evolution of sound reception mechanisms among echolocating species. Despite possible autolytic artifacts due to technical and experimental constraints, the SEM analysis allowed us to detect the presence of scarring processes resulting from the disappearance of outer hair cells from the epithelium. In addition, in contrast to the rapid decomposition process of the sensory epithelium after death (especially of the inner hair cells), the tectorial membrane appeared to be more resistant to postmortem autolysis effects. Analysis of the stereocilia imprint pattern at the undersurface of the tectorial membrane may provide a way to detect possible ultrastructural alterations of the hair cell stereocilia by mirroring them on the tectorial membrane. J. Comp. Neurol. 523:431–448, 2015. © 2014 Wiley Periodicals, Inc.